Unveiling Intangible Factors in Tourism: A Case of Gandaki Province, Nepal - Sapkota, Pradeep (Journal of Business and Management, 2024)
Background: Tourist satisfaction reflects the degree to which visitors are pleased with their travel experiences, encompassing both tangible and intangible aspects of tourism. Understanding these factors is essential for destinations seeking to enhance visitor experiences and promote repeat visits.Objectives: This study investigates the intangible factors that influence tourist satisfaction and revisit intentions among international and domestic visitors to Gandaki Province, Nepal, aiming to identify elements that can enhance the destination’s appeal. Methods: This study followed descriptive as well as causal comparative research design. A sample of 616 respondents was drawn from three districts within Gandaki Province, with data gathered through a self-administered questionnaire. Statistical analysis was conducted using IBM SPSS, incorporating methods such as Means, Standard Deviation (SD), Exploratory Factor Analysis (EFA), and Structural Equation Modelling (SEM) to evaluate relationships among variables.Results: The statistical analysis indicated that intangible factors such as nature, culture, and hospitality have a significant influence on tourist satisfaction and their intention to revisit Gandaki Province. Among these factors, hospitality was identified as the most influential element driving tourist satisfaction. In contrast, cultural experiences were found to be the most compelling reason for tourists’ intentions to return.Conclusion: The study concludes that enhancing intangible elements like hospitality and cultural offerings can substantially boost tourist satisfaction and encourage repeat visits to Gandaki Province. By prioritizing these areas, destination managers and policymakers can strengthen Gandaki Province’s appeal as a tourism destination, contributing to a more sustainable tourism environment.JEL Classification: M31, L83, Z10